First night effect alters occipital brain connectivity in horses - Jürgen Bergeler; Astrid Liske-Schmitz; Thomas Schmitz; Nora Vanessa de Camp (Scientific Reports)
Abstract The First Night Effect is a phenomenon whereby sleep duration and quality are compromised in unfamiliar environments or situations. Horses are often transported to new locations, such as sporting events. We wanted to know if the First Night Effect is also detectable in horses in two different populations. To investigate this, we compared five horses from a professional sports horse barn that are regularly used in competitions, with six horses from a breeding barn, that are less frequently transferred to unfamiliar places. Despite the significant differences observed in electroencephalography (EEG) patterns and behavior between the two horse populations, we were able to identify EEG changes indicative of the First Night Effect. These changes were most apparent in the delta band at the occipital position of the brain, indicating fluctuations in sleep-wake dynamics and consciousness. Furthermore, in this study, EEG data outperformed behavioral data in the detection of the First Night Effect, indicating the usefulness of EEG measurements for monitoring welfare or even assessing stress and pain.